TINJAUAN HUKUM ISLAM TERHADAP PENITIPAN ORANG TUA OLEH ANAK DI PANTI SOSIAL TRESNA WERDHA SABAI NAN ALUIH SICINCIN KABUPATEN PADANG PARIAMAN - Abdi, Syafral; Bahar, Muchlis (UIN Imam Bonjol Padang, 2020)
This study aims to describe the care of parents by children at the Tresna Werdha Social Home (PSTW) Sabai Nan Aluih Sicincin and to review the care of parents by children in social institutions from the perspective of Islamic law. This study uses data collection by interview and observation, as well as supporting documents to be used as references in the preparation of this thesis. The type of research used in this writing is field research and the approach used in this research is normative, namely an approach to determine the status of Islamic law in parental care. The results of this study, there are two reasons why children entrust their parents to PSTW: First, due to the wishes of the parents themselves. Second, not because of the parents' own wishes, such as: not wanting to burden the family, looking for friends and wanting to be calm, less harmonious, losing roles, neglected at home and economic factors. The reality experienced by parents in the orphanage is divided into two situations. First, parents feel happy. Apart from being able to gather with peers, parents also receive special care with adequate facilities. Second, parents who do not get happiness, this is because parents do not fit into the environment of the orphanage, and the presence of parents in the orphanage is not of their own accord. Even so, when it is analyzed from a review of Islamic law, children who leave their parents at the Tresna Werdha Sabai Nan Aluih Sicincin, Social Home are three levels of law that discuss the law of child care for parents in PSTW. If the wishes of the parents themselves, then the law is makruh, whereas if forced by circumstances the law is permissible, but if children leave their parents because they do not want to take care of their parents, while they are self-sufficient, then the law is haram.Keywords: PSTW, Parents, Law, Islam